Darkness into light? Identification with the crowd at a suicide prevention fundraiser promotes well‐being amongst participants. (3rd October 2017) - Kearns, Michelle; Muldoon, Orla T.; Msetfi, Rachel M.; Surgenor, Paul W. G.
Abstract: Suicide is recognised to be subject to social contagion, with an elevated risk of adverse outcomes amongst those affected. Drawing upon research within the social identity approach, we hypothesised that, for those bereaved by suicide, identifying with similar others could provide 'a social cure'. A large cross‐sectional study and a longitudinal study were carried out at a charity fundraiser for suicide prevention, with participants completing an online survey before and after the event. Results showed that, for those who lost someone they knew (Study 1) or a family member (Study 2) to suicide, there was a significant increase in psychological well‐being after the event. This was mediated by identification with the crowd. These findings demonstrate that collective participation in a suicide awareness event can be an effective social intervention for those bereaved by suicide in terms of psychological well‐being, with implications for informing best‐practice interventions targeting this at‐risk group.